Порівняння як засіб репрезентації концепту ПРИРОДА (на матеріалі творів німецькомовних письменників Галичини) - Радченко, Олег Анатолійович; Дашко, Наталія Тарасівна; Radchenko, O. A.; Dashko, N. T. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено вивченню порівнянь, які вербалізують концепт ПРИРОДА, з позиції когнітивної лінгвістики, що дає змогу дослідити особливості концептуальної картини світу німецькомовних письменників Галичини. Здійснено комплексний аналіз об’єктиваторів досліджуваного концепту, вивчено їхню структуру та особливості функціонування в тексті. З’ясовано, що під час вербалізації концепту ПРИРОДА зазвичай вико¬ристовують гомогенні порівняння, у яких зіставлення відбувається за фізичними характеристиками явищ природи чи за поведінкою представників тваринного світу. The article examines the comparisons verbalizing the concept NATURE used in Galician German-speaking writers' creative works. It is ascertained that, grammatically, the comparisons are represented by comparative composites, comparative phrases, and subordinate clauses of unreal comparison. When verbalizing the concept NATURE, homogeneous comparisons performing comparison by physical characteristics of nature phenomena or by animal behavior are used. Peculiar author's comparisons that help to explore the conceptual picture of the world seen by the writer are relevant for Cognitive Linguistics. As the components of figurative comparisons bear emotional content, this kind of comparisons is marked by the highest expression. Frequent usage of comparisons in the texts involved could be explained by their capacity to express the author’s unique world-view and to influence the reader’s perceptional, estimating, and emotional spheres.
Comparison as a Mean of Representation of the Concept NATURE (illustrated by the materials of creative works of German-speaking writers of Galicia)
Keywords: порівняння; comparison; концепт; concept; природа; nature